MULTIFACTOR CLUSTER ANALYSIS OF FOREIGN TRADE INDICATORS (EXAMPLE OF UZBEKISTAN) (Marketing Journal, 2025)
This study provides an in-depth analysis of Uzbekistanʼs foreign trade processes through the application of clustering methods aimed at ensuring more efficient resource utilization and developing practical policy recommendations. Based on official data from the State Committee on Statistics and the World Bank, the k-means and hierarchical cluster analysis techniques were employed. The analysis evaluated key indicators such as export and import volumes, the RCA index, trade balance, and 203 growth rate, which are identified as the main determinants of Uzbekistanʼs trade performance. The research results demonstrate that clustering analysis of foreign trade indicators enables a systematic evaluation of trade efficiency, identification of underlying determinants, and formation of a methodological foundation for evidence - based economic policymaking.
Keywords: Export volume; import volume; RCA; k-means clustering; hierarchical clustering